2001
DOI: 10.1002/jso.1093
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐lymph node metastasis and its correlation with cathepsin D expression in early gastric cancer

Abstract: The acidic protease CD may play an important role of cancer metastasis in EGC. The limited operation without lymphadenectomy should be indicated for EGC with CD-negative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…In early gastric cancer, cathepsin D activates micro-lymph node metastasis [67], and studies have shown that human telomerase reverse transcriptase (hTERT) can stimulate cathepsin D expression by activating early growth response protein 1 (an important nuclear transcription factor that can promote cell proliferation), thereby inducing cancer cell invasion [68]. Anterior gradient 2 (AGR2), a p53 suppressor that is widely expressed in many tumors, is known to stimulate the proliferation and development of cancer cells.…”
Section: Gastric Cancermentioning
confidence: 99%
“…In early gastric cancer, cathepsin D activates micro-lymph node metastasis [67], and studies have shown that human telomerase reverse transcriptase (hTERT) can stimulate cathepsin D expression by activating early growth response protein 1 (an important nuclear transcription factor that can promote cell proliferation), thereby inducing cancer cell invasion [68]. Anterior gradient 2 (AGR2), a p53 suppressor that is widely expressed in many tumors, is known to stimulate the proliferation and development of cancer cells.…”
Section: Gastric Cancermentioning
confidence: 99%
“…[1][2][3] Occult metastasis at the time of operation is an important cause of cancer recurrence. Another possibility leading to cancer recurrence is the fact that surgical manipulation may spread cancer cells from the main tumor into a patient's blood vessels.…”
Section: Introductionmentioning
confidence: 99%
“…15,23,24 Subsequently, it has been recommended that levels of CD be monitored as a prognostic indicator in breast cancer and used independent of classical prognostic parameters such as tumor size, histological grade, lymph node status, and steroid receptor expression. 25 -27 The significance of pCD and CD levels in other tumors such as endometrial adenocarcinoma, 28,29 colon carcinoma, 30 colorectal carcinoma, 31 oral cancer, 32 laryngeal tumors, 33,34 head and neck squamous cell carcinoma, 35 carcinoma of thyroid tissue, 36 prostate tumors 37,38 melanoma, 8,39 gastric cancer, 40 and ovarian cancer, 41,42 has also been demonstrated, suggesting that this system might be involved in the metastatic growth of numerous other cancer cell types.…”
mentioning
confidence: 99%